Prospective external validation of a new non‐invasive test for the diagnosis of non‐alcoholic steatohepatitis in patients with type 2 diabetes. Issue 7 (16th August 2021) - Poynard, Thierry; Paradis, Valérie; Mullaert, Jimmy; Deckmyn, Olivier; Gault, Nathalie; Marcault, Estelle; Manchon, Pauline; Si Mohammed, Nassima; Parfait, Beatrice; Ibberson, Mark; Gautier, Jean‐Francois; Boitard, Christian; et al.
Summary: Background: One of the unmet needs in patients with type 2 diabetes mellitus (T2DM) is the prediction of non‐alcoholic liver disease by non‐invasive blood tests, for each of the three main histological features, fibrosis, non‐alcoholic steatohepatitis (NASH) and steatosis. Aims: To validate externally the performances of a recent panel, Nash‐FibroTest, for the assessment of the severity of fibrosis stages, NASH grades and steatosis grades. Methods: We prospectively analysed 272 patients with T2DM. Standard definitions of stages and grades were used, and analyses were centralised and blinded. The performances of the FibroTest, NashTest‐2 and SteatoTest‐2 were assessed using the Obuchowski measure (OM), the main outcome recommended as a summary measure of accuracy includeing all pairwise stages and grades comparisons, which is not provided par the extensively used binary area under the ROC curve. Results: The diagnostic performance of each component of the panel was significant. OM (SE; significance) of the FibroTest, the NashTest‐2 and the SteatoTest‐2 was 0.862 (0.012; P < 0.001), 0.827 (0.015; P < 0.001) and 0.794 (0.020; P < 0.01), respectively. For ballooning and lobular inflammation, OM was 0.794 (0.021; P < 0.001) and 0.821 (0.017; P < 0.001), respectively. In a post hoc analysis the FibroTest outperformed VCTE by 4.1% (2.5‐6.5; P < 0.001) for reliability, with a non‐significant difference for OM for fibrosis staging, 0.859 (0.012) for FibroTest vs 0.870 (0.009) for VCTE. Conclusions: From a single blood sample, the panel provides non‐invasive diagnosis of the stages of fibrosis, and the grades of NASH and steatosis in patients with T2DM. Trial registration number: NCT03634098. Abstract : From a single blood sample, the Nash FibroTest panel provides non‐invasive diagnosis of the stages of fibrosis and the grades of NASH, including ballooning and lobular inflammation, and steatosis grades in patients with type 2 diabetes mellitus.